GREY WATER FARMING OF LADIES FINGER AND CLUSTER BEANS-INDUCES DIETARY TOXICITY? - Yashwant, Doke Suraj; Mohan, Chavare Pranav; Adavirao, Belvotagi Venkatrao (International Journal of Current Pharmaceutical Research, 2017)
Objective: A large number of farmers are growing different vegetables and supplying them to the Solapur market. The majority of these farms are located on the banks of the nullahâ€, whose water is used for irrigation. From, a farm field in Degaon, a village on the Solapurâ€“Mangalvedha road and on the bank of â€˜nullah' two fruit vegetables viz., Ladies Finger (Bhendi) and Cluster Beans (Gawar) are evaluated in the study. The purpose of this study was to analyse the presence of selected toxic non-essential heavy metals i.e. Arsenic (As), Cadmium (Cd), Chromium (Cr), Lead (Pb) and Mercury (Hg) in the two vegetables. Methods: Atomic Absorption Spectrophotometer (AAS) was used for determining the concentration of heavy metals. Optimised wet acid digestion procedure was employed to solubilize the metals from the vegetable samples. Results: The following concentrations (mg/kg) of the non-essential heavy metals were found in the edible parts of the Ladies Finger and Cluster Beans, respectively: Ladies Finger: As (16.07), Hg (16.77), Pb (1.148), Cr (17.14), Cd (0.704 mg/kg) and Cluster Beans: As (18.76), Hg (21.86), Pb (1.675), Cr (17.14), Cd (0.888 mg/kg). The study revealed the presence of all the chosen NEHMs in the vegetables. Cadmium levels in both Cluster Beans and Ladies Finger were below the maximum acceptable limit and hence fit for human consumption as per FSSAI standards As (1.1), Pb (1.0), Cd (1.5), Hg (1.0 ppm). Though unsafe as per WHO/FAO standards As (0.1), Pb (0.5), Cd (0.2), Cr (1.2), Hg (0.05 ppm). Conclusion: The other three NEHMs levels were approximately 15 times more than the permitted levels and hence might pose danger on human consumption. Â